Relationship between Work-Family Conflict and Intention to leave among Nurses - F Sharifzadeh; A Mohammadi Mahmouei; H Alizadeh; S Khani Pordanjani; F Heshmati (Iran University of Medical Sciences, 2014)
Abstract   Background & Aim: Nowadays hospitals bear with the financial and human costs because of nurses' turnover. Many factors affect nurses' turnover and work-family conflict is one of these variables. Thus, the purpose of this study is determining the relationship between work-family conflict and intention to leave among nurses.   Material & Methods: It was a descriptive, cross-sectional study. A total of 257 nurses working in Emam Khomeini, Firouzgar, and Day & Hashemi Nejad hospitals in Tehran who were selected by stratified random sampling participated in the study. Data was gathered via Carlson et al. and Tei & Yamazakei standard questionnaires. Data analysis performed by Structural Equation Modeling, Path Analysis, and Independent T-Test via LISREL and SPSS-PC (v.16).   Results: Path Analysis showed that work-family conflict had a positive significant relationship (β= 0.9 ) with intention to leave among nurses (P<0.01). Pearson correlation test showed that there is a positive significant relationship between gender and work-family conflict (P<0.05, r=0.13), Intention to leave and age (P<0.05, r=0.15) and years of work experience (P<0.01, r=0.17). Also we found that work-family conflict in public hospitals was more than private hospitals (P=0.02). However, there was no significant difference between intention to leave in public and private hospitals (P=0.66). Conclusion: Recognition of nurses' work-family conflict can play an important role in reducing the consequences and negative outcomes such intention to leave among nurses and provide an efficient basis to adopt effective strategies for human resource management.